2020
DOI: 10.1101/2020.07.23.217109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spotting genome-wide pigmentation variation in a brown trout admixture context

Abstract: Colour and pigmentation variation attracted fish biologists for a while, but high-throughput genomic studies investigating the molecular basis of body pigmentation remain still limited to few species and conservation biology issues ignored. Using 75,684 SNPs, we investigated the genomic basis of pigmentation pattern variation among individuals of the Atlantic and Mediterranean clades of the brown trout (Salmo trutta), a polytypic species in which Atlantic hatchery individuals are commonly used to supplement lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 220 publications
(266 reference statements)
0
7
0
Order By: Relevance
“…F 1 offspring of gillaroo and sonaghen reared in separate small lakes s c150 km from Lough Melvin demonstrate the stability of their pigmentations patterns even under distinct environmental and feeding conditions (Figure 1). Genomic data are increasingly demonstrating the genetic bases of colouration differences in Eurasian trout (Valette et al, 2020). Stepwise discriminant analysis based on 12 meristic counts and 19 morphometric measurements from the three morphs correctly assigned 100% of the ferox, 98.8% of gillaroo and 98.7% of sonaghen (Cawdery & Ferguson, 1988).…”
Section: Lough Melvinmentioning
confidence: 99%
“…F 1 offspring of gillaroo and sonaghen reared in separate small lakes s c150 km from Lough Melvin demonstrate the stability of their pigmentations patterns even under distinct environmental and feeding conditions (Figure 1). Genomic data are increasingly demonstrating the genetic bases of colouration differences in Eurasian trout (Valette et al, 2020). Stepwise discriminant analysis based on 12 meristic counts and 19 morphometric measurements from the three morphs correctly assigned 100% of the ferox, 98.8% of gillaroo and 98.7% of sonaghen (Cawdery & Ferguson, 1988).…”
Section: Lough Melvinmentioning
confidence: 99%
“…Knowledge of the genetics that underpin the manifestation of various chromatypes or phenotypes of skin pigmentation has been based on qualitative traits through studies on natural or artificially activated colour mutants in species of fish that are used as models for study including zebrafish, Danio rerio [6] and medaka, Oryzias latipes [7]. Studies have shown that the genetic basis of skin pigmentation in fish can be any of monogenetic [8], polygenetic [9], pleiotropic and sex-linked [10,11]. The evidence from these studies overwhelmingly supports the involvement of several genes in the manifestation of a particular skin colour or colour pattern through modulation of chromatophores that lead to synthesis and expression of pigments.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RDA in genomewide association studies (GWAS) in animal breeding is not common. However, RDA is a powerful approach that can be utilized in GWAS studies in livestock (Kess and Boulding, 2019;Torrado et al, 2020;Valette et al, 2020). Phenotype association analysis was performed with RDA to explain variation in the genome associated with five quantitative traits (mature live body weight, beak length, comb width, wattle width and earlobe width).…”
Section: Discussionmentioning
confidence: 99%
“…Signatures of selection analysis identify regions of the genome that have differentiated between populations, possibly in response to selective pressure (Sabeti et al, 2006;Voight et al, 2006). Multivariate methods that simultaneously account for multiple drivers of phenotypic and environmental divergence, are recently being applied in landscape genomic studies to identify quantitative trait loci (QTL) associated with environment predictors (Forester et al, 2018;Harrisson et al, 2017;Kess and Boulding, 2019;Torrado et al, 2020) and with phenotypic variables (Carvalho et al, 2021;Kess and Boulding, 2019;Talbot et al, 2017;Valette et al, 2020;Vangestel et al, 2018). Multivariate ordination methods such as RDA have outperformed mixed-modelbased methods and machine learning-based methods (e.g., Random Forest) in detecting loci associated with environmental variation (Capblancq et al, 2018;Forester et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation